Automatic Braking System Using Fuzzy Logic Bassed on Microcontroller - Aris Munandar (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2016)
In the automatic braking system is used fuzzy logic control to determine the value of the percentage of the brakes to be done. For input on fuzzy logic itself in the form of speed when driving the car on the distance between the car and the obstacle in front of him. The number of rules used in the fuzzy logic control totaling 28 .Rule contains a comparison between the speed of the car while driving and the distance between the obstacle in front of the car so as to produce brake percentage value that corresponds to the condition of the car while driving. Automatic braking system design is made in the form of a prototype car using Atmega microcontroller 32 as a processor. By using fuzzy logic with 28 rule, systems are made to be able to do better braking when the car drove at low speed or driving at high speed with a stopping distance of about ± 10cm up to ± 5cm. In addition, the system is designed not affect the car to be able to pass through a narrow area such as a garage, with the distance between the obstacle and the right part of the left side approximately ± 2cm.